Variability of genetic - morphological traits of eleven seed strains of Mangifera indica L. growing in Upper Egypt - Hoida ZAKI; Mona Mohamed MANSOUR; Samah Osman Ahmed OSMAN; Nagwa Rabie Ahmed HUSSEIN (Acta Agriculturae Slovenica, 2023)
Mango (Mangifera indica L.) is one of the tastiest fruits in the world, with numerous advantages beyond their economic value. Eleven genotypes of mango various cultivars were examined for variability, heritability, and genetic advance, as well as multivariate analysis based on cluster and principal component analysis (PCA) for yield and some of its contributing traits during the two growing seasons, 2021 and 2022. All studied traits showed significant differences, and the phenotypic coefficients of variation (PCV) were found to be higher than genotypic coefficients of variation (GCV), supporting the idea that morphological (genetic) traits are more prevalent than environmental influence. All traits had substantial heritability ranging from 75.63 to 99.93 %, and the highest significant genetic advance (119.09 %) was for the number of fruits per tree than other traits. Four clusters were formed, i.e., clusters I and IV had four genotypes, cluster II had two, and cluster III had one genotype. The highest cluster mean values for fruit diameter, fruit mass, yield per tree, and the number of fruits per tree were found in Cluster II, followed by cluster I. Greater genetic divergence was found between ‘Zebda’  or ‘S9’ or ‘S10’ with most other genotypes, indicating that these genotypes may be used to study the characters’ broad range of variability and to yield high-quality recombinant lines. In light of the fact that mango is a very heterozygous crop, our current genetic results can be used for the selection of the appropriate parents in hybridization programs and in vegetative propagation to yield selective traits.